Drug-eluting balloons and drug-eluting stents in the treatment of small vessel coronary artery disease: a systematic review and metanalysis of long-term clinical and angiographic outcomes. (3rd October 2022) - Murphy, G; Durand, R; McCaughey, C; Naughton, A; Heron, E; Pearson, I
Abstract: Introduction: Coronary artery disease is a leading cause of mortality and morbidity worldwide. For those undergoing PCI, there are 20–30% with disease of the small coronary arteries on presentation [1]. Small coronary artery disease asserts a significant risk factor for adverse events. It is often diffuse and multi-vessel on presentation and confers higher rates of major adverse cardiac events, (MACE) and target lesion failure after intervention [2, 3]. Best practice guidelines on the management of SvCAD interventions remain limited. Drug-eluting balloons are a novel therapy, which has shown promise in treating in-stent restenosis (ISR), however their use in small coronary arteries when compared to drug-eluting stents remains unclear. Purpose: This systematic review and meta-analysis compare long-term outcomes (>1 year), of drug-eluting balloons (DEB), vs. drug-eluting stents (DES), in the treatment of small coronary artery disease (<3mm). Methods: A systematic review was completed within PRISMA guidelines. The primary outcome was non-inferiority of DEB Vs. DES in major adverse cardiac events (MACE). Secondary outcomes include all-cause mortality, MI, vessel thrombosis, major bleeding and target vessel revascularization at one, two and three years follow-up. Two independent reviewers extracted data. All outcomes used the Mantel-Haenszel and Random effect model. Odds ratios (OR), were presented with a 95% confidence interval (CI). Result: Of 4661 articles, four RCTs were included (1414 patients). DEB demonstrated reduced rates of non-fatal MI at one year, OR 0.44 (95% CI 0.2, 0.94) and Basket-2 small reported a significant reduction in two-year bleeding rates OR 0.3 (95% CI 0.1, 0.91). DEBs were non-inferior to DES for all other outcomes. Conclusion: Long duration follow-up of DEB and DES use in small coronary arteries demonstrates DEB to be non-inferior to DES in all outcomes across all years of follow-up. There was a significant reduction in rates of non-fatal MI at one year in the DEB arm and a reduction in major bleeding episodes at two years in the Basket Small 2 trial. These data highlight the potential utility and long-term safety of novel DEBs in small coronary artery disease revascularization. Funding Acknowledgement: Type of funding sources: None.